Studying human respiratory disease in animals – role of induced and naturally occurring models. Issue 2 (January 2016) - Williams, Kurt; Roman, Jesse
Abstract: Respiratory disorders like asthma, emphysema, and pulmonary fibrosis affect millions of Americans and many more worldwide. Despite advancements in medical research that have led to improved understanding of the pathophysiology of these conditions and sometimes to new therapeutic interventions, these disorders are for the most part chronic and progressive; current interventions are not curative and do not halt disease progression. A major obstacle to further advancements relates to the absence of animal models that exactly resemble the human condition, which delays the elucidation of relevant mechanisms of action, the unveiling of biomarkers of disease progression, and identification of new targets for intervention in patients. There are currently many induced animal models of human respiratory disease available for study, and even though they mimic features of human disease, discoveries in these models have not always translated into safe and effective treatments in humans. A major obstacle relates to the genetic, anatomical, and functional variations amongst species, which represents the major challenge to overcome when searching for appropriate models of respiratory disease. Nevertheless, rodents, in particular mice, have become the most common species used for experimentation, due to their relatively low cost, size, and adequate understanding of murine genetics, among other advantages. Less well known is the fact that domestic animals also suffer from respiratory illnesses similar to those found in humans. Asthma, bronchitis, pneumonia, and pulmonary fibrosis are among the many disorders occurring naturally in dogs, cats, and horses, among other species. These models might better resemble the human condition and are emphasized here, but further investigations are needed to determine their relevance. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.